Is spatial bootstrapping a panacea for valid inference? - Torben Klarl (Universität Augsburg, Institut für Volkswirtschaftslehre, 2013)
Bootstrapping methods have so far been rarely used to evaluate spatial data sets. Based on an extensive Monte Carlo study we find that also for spatial, cross-sectional data, the wild bootstrap test proposed by Davidson and Flachaire (2008) based on restricted residuals clearly outperforms asymptotic as well as competing bootstrap tests, like the pairs bootstrap.
urn:nbn:de:bvb:384-opus4-710952
Keywords: C18; C21; R11; 330; Spatial econometrics; Paired bootstrap; Wild bootstrap; Parameter inference